RELATIONS AMONG FORAGE SHORGUM YIELD AND PHYSICAL ATTRIBUTES AND ORGANIC MATTER CONTENT OF A LATOSOL IN THE BRAZILIAN SAVANNAH - Basso, Fernanda Carvalho (2011)
The soil physical attributes and organic matter influence plant growth and development by limiting root growth and crop yield. Aiming to study the spatial and linear correlations among forage sorghum yield and soil physical properties and organic matter, an experiment was carried out in a Distroferric Red Latosol, in Selvíria, Mato Grosso do Sul State, Brazil, in the 2005 crop season. Thus, the forage sorghum fresh and dry matter yield, microporosity, macroporosity, total porosity, soil bulk density, and organic matter content were analyzed, at three depths (0.00-0.10 m, 0.10-0.20 m, and 0.20-0.30 m). The samples were collected in a geostatistical grid, with a total of 124 points, in an area of 4,000 m2. The sorghum fresh and dry matter yield showed high variability, while, for the soil properties, it was low. The plant attributes, macroporosity (in the first layers), microporosity, total porosity, and bulk density, in the first and third layers, followed well-defined spatial standards, reaching from 17.9 m to 84.2 m, while the other attributes showed pure nugget effect. The simple linear correlation among the plant attributes was high and positive, while among the plant and soil attributes it was low and significant, with positive interactions for macroporosity and total porosity, as well as negative for soil bulk density, in the first layer. The bulk density in the soil surface layer was an excellent indicator of soil physical quality, for the estimation of dry matter yield.KEY-WORDS: Spacial variability; macroporosity, microporosity, total porosity; bulk density.